Molecular insights into the therapeutic mechanisms of Bushen-Qiangdu-Zhilv decoction for ankylosing spondylitis - Ma, Mengyang; Yang, Zhihua; Li, Ke; Yang, Lu; Chen, Bozhen; Chen, Meiqi; Du, Haifang; Zhou, Yingyan; He, Xiaohong; He, Yiting (Journal of ethnopharmacology, 2024)
Ethnopharmacological relevance - Ankylosing spondylitis (AS) is a chronic rheumatic immune disease characterized by high disability rates, significantly affecting patients' quality of life. BuShen-QiangDu-ZhiLv Decoction (BQZD), developed by the renowned traditional Chinese medicine practitioner Jiao Shude, has been traditionally used for AS treatment. However, the bioactive components and the precise mechanisms underlying BQZD's therapeutic effects remain largely unexplored. - Aim of the study - To investigate the protective effects and elucidate the molecular mechanisms of BQZD in treating ankylosing spondylitis. - Materials and methods - Ultra Performance Liquid Chromatography coupled with tandem mass spectrometry (UPLC-MS/MS) was used to identify active compounds in BQZD. Bulk RNA-seq and Gene Set Variation Analysis (GSVA) were conducted to assess changes in pathway activity in AS patients before and after three months of BQZD treatment. We also utilized network pharmacology and molecular docking analyses to predict potential mechanisms, identifying key target genes such as IL-6, NFATc1, and c-FOS. Animal experiments were performed to validate these findings. - Results - UPLC-MS/MS identified 28 active compounds in BQZD capable of entering the bloodstream, with potential anti-inflammatory, immunomodulatory, and bone metabolism-regulating effects. BQZD treatment led to a significant reduction in ESR, CRP, and ASDAS-CRP scores, indicating clinical improvement in AS patients. RNA-seq analysis showed decreased GSVA scores for the ossification pathway, with moderate reductions in inflammatory response and RANKL signaling pathways. Positive correlations were found between pathway activity and clinical indicators. Network pharmacology and transcriptomic analysis identified IL-6, NFATc1, and c-FOS as key targets. In vivo experiments confirmed that BQZD reduced TNF-α and IL-1β levels, inhibited ectopic ossification, and modulated the expression of DKK-1, MMP-9, and OPN in the CAIA model. - Conclusions - BQZD exerts therapeutic effects in AS by regulating inflammation and abnormal ossification through multi-pathway, multi-target mechanisms. The identification of key target genes such as IL-6, NFATc1, and c-FOS provides a solid foundation for future research and clinical applications of BQZD in AS management.